Meningkatkan Kemampuan Berhitung Siswa Melalui Simulasi University War Berbantuan Multiplication Bingo Game - Nurfia; Aisyah Nursyam; Andi Muhammad Irfan Taufan Asfar; Andi Trisnowali MS. (Rengganis Jurnal Pengabdian Masyarakat, 2025)
This community engagement program aimed to improve elementary school students’ arithmetic skills through the University War simulation assisted by the Multiplication Bingo Game. The activity was conducted at SD Negeri 01 Kwangsan using the Participatory Action Research (PAR) method, which involved five stages: identifying problems, understanding the context, planning solutions, taking action, and reflecting. The simulation was based on the cooperative learning model Teams-Games-Tournament (TGT), designed to foster student engagement in a fun and competitive environment. Wilcoxon test results indicated a significant improvement in students' arithmetic performance after the intervention. Furthermore, survey responses showed that most students felt more confident, motivated, and found multiplication concepts easier to understand. This program had a positive impact on creating an interactive and effective mathematics learning experience, and it is recommended for ongoing integration into classroom instruction.